Sex Differences in Hypothalamic Changes and the Metabolic Response of TgAPP Mice to a High Fat Diet - Freire-Regatillo, Alejandra; Diaz-Pacheco, Sonia; Frago, Laura M.; Arévalo, María-Ángeles; Argente, Jesús; Garcia-Segura, Luis M.; de Ceballos, María L.; Chowen, Julie A. (Frontiers in Neuroanatomy, 2022)
The propensity to develop neurodegenerative diseases is influenced by diverse factors including genetic make-up, sex, lifestyle, including dietary habits and being overweight, and age. Indeed, with aging there is an increased incidence of both obesity and neurodegenerative processes, both of which are associated with inflammatory processes, in a sex specific manner. Although aging-induced modifications in sex steroids and increased cell stress are involved, there is a complex interaction between these process that remains to be understood. Here we have analyzed the metabolic and inflammatory responses of middle-aged transgenic amyloid precursor protein (TgApp) mice of both sexes to a high fat diet (HFD) for 18 weeks. We found clear sex differences with females gaining significantly more weight and fat mass than males, in addition to a larger increase in circulating leptin levels and expression of inflammatory markers in visceral adipose tissue. However, glycemia and insulin levels increased in HFD fed mice of both sexes, with TgAPP mice being more affected than wild type (WT) mice. In the hypothalamus, amyloid β levels were increased by HFD intake exclusively in males and reaching statistical significance only in APP males. On a low fat diet (LFD), TgAPP males had significantly lower mRNA levels of the anorexigenic neuropeptide proopiomelanocortin (POMC) than WT males, with HFD intake decreasing the expression of the orexigenic neuropeptides Agouti related peptide (AgRP) and neuropeptide Y (NPY), especially in TgAPP mice. In contrast, in females there was no effect of genotype on these metabolic neuropeptides, with HFD increasing POMC mRNA levels but with no effect on AgRP or NPY mRNA levels. We found no effect of diet or genotype on the inflammatory markers analyzed in the hypothalamus. Likewise, no differences in glial acidic protein (GFAP) levels were found; however, there was an increase in the levels of the microglial marker Iba1 selectively in male TgAPP mice. Together these data indicate that there is a complex interaction between sex and the expression of APP on the hypothalamus and the metabolic response to high fat diet intake.